2009
DOI: 10.1007/s11244-009-9270-9
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Catalytic Transformation of Citronellal to Menthol in a Single Step on Ir-Beta Zeolite Catalysts

Abstract: The synthesis of menthol from citronellal was studied on bifunctional Ir/Beta zeolite catalysts, prepared via impregnation of Beta zeolite with different concentrations of Ir. The results show that Beta zeolites, impregnated with Ir, catalyze the one-pot full conversion of citronellal to menthol by consecutive acid-catalyzed cyclization and Ir-catalyzed hydrogenation. The best results (95% selectivity for the menthol isomers, of which 75% is the desired (±)-menthol) were recorded on 3% Ir/Beta zeolite catalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 28 publications
5
31
1
4
Order By: Relevance
“…To afford citronellal transformation into menthol in a one-pot, a bifunctional catalyst bearing acid and metal sites can be used. Jacobs et al 23,24 have reported that a 3% Ir-impregnated H-BEA zeolite catalyzes the one-pot synthesis of menthol from citronellal in two steps. First, the cyclization step was carried out under N 2 atmosphere, and then H 2 was added to carry out the hydrogenation.…”
Section: Introductionmentioning
confidence: 99%
“…To afford citronellal transformation into menthol in a one-pot, a bifunctional catalyst bearing acid and metal sites can be used. Jacobs et al 23,24 have reported that a 3% Ir-impregnated H-BEA zeolite catalyzes the one-pot synthesis of menthol from citronellal in two steps. First, the cyclization step was carried out under N 2 atmosphere, and then H 2 was added to carry out the hydrogenation.…”
Section: Introductionmentioning
confidence: 99%
“…Ir(III), in the Beta zeolite (entry 11) clearly increases the reaction rate. 11 Therefore, the presence of strong Lewis acid sites in a hydrophobic environment is decisive for the high catalytic activity of these Sn o Zr Beta zeolites, compared to MOFs, as will be confirmed in the following section.…”
Section: Francisco G Cirujano (Born In Alcoy In 1987) Obtained the Bmentioning
confidence: 61%
“…Hal tersebut mendorong para peneliti melakukan upaya penggantian situs asam Bronsted dengan situs asam Lewis dengan cara mengembankan logam aktif. Penelitian sebelumnya mengenai katalis berbasis pengemban β-zeolit untuk konversi sitronelal telah banyak dilaporkan, antara lain adalah Ni/Zr-beta (Nie et al 2007), katalis Pt/H-beta yang dapat berperan sebagai katalis dwi fungsi (Mertens et al 2006), katalis Sn/β-zeolit yang memberikan stereoselektivitas 85% (Kang et al 2013), dan katalis Ir/ β-zeolit yang memberikan produk mentol yang tinggi (93%) dalam reaksi satu tahap (Dirk dan Jacobs 2009).…”
Section: Pendahuluanunclassified